ETHNO-LITERACY ANALYSIS OF INDONESIAN HIGH SCHOOL TEXTBOOKS AND LOCAL CULTURE REPRESENTATION - Linda Eka Pradita; Sri Wulandari; ‘Aqilah Khairunnisa, Nasywa; Imam Nur Muttakin (Jurnal Ilmiah Bina Bahasa, 2025)
Teaching books as learning resources are developed to achieve educational goals. The achievement of educational goals is related to the feasibility of the content of teaching books. Aligning teaching books with educational objectives requires analysis to assess quality. The purpose of the study is to determine the feasibility of ethno-literacy materials and its in Indonesian language textbooks. This study uses the content analysis method with the Indonesian language textbook entitled “Buku Cerdas Cergas Berbahasa dan Bersastra Indonesia SMA/SMK/MA 2022 as the data source.” The data collection technique uses document analysis from various written sources relevant to the textbook. The data analysis technique to determine the ethno-literacy content of Indonesian language textbooks uses a content analysis scheme. The research results integrating elements of local wisdom into open textbooks, so students can better understand and preserve the nation's culture. Ethno-literacy content in textbooks can help students understand and appreciate differences in ethnicity, language, and culture. When students study ethno-literacy-based texts, they not only understand the content but also analyze the values contained within. This encourages students to think critically about culture. Integrating ethno-literacy content into textbooks can increase reading motivation. Stories or texts containing local cultural elements are more engaging for students because they relate to their lives. This can increase students' interest in reading and their understanding of literacy. Ethno-literacy content in textbooks represents local culture to maintain diversity. By integrating local culture into learning materials, textbooks can serve as a medium for preserving local culture while enhancing students' understanding of cultural diversity.